The updated Swiss guidelines 2016 for the treatment and follow-up of cutaneous melanoma - Dummer, Reinhard; Siano, Marco; Hunger, Robert E.; Lindenblatt, Nicole; Braun, Ralph; Michielin, Oliver; Mihic-Probst, Daniela; Von Moos, Roger; Najafi, Yousef; Guckenberger, Matthias; Arnold, Andreas (Swiss medical weekly, 2016)
Cutaneous melanoma is the most deadly cutaneous neoplasm. In order to guide treatment decisions and follow-up of melanoma patients, guidelines for the management of melanoma in Switzerland were inaugurated in 2001 and revised in 2006 and 2016. Recent data on surgical and medical treatments from randomised trials necessitated modification of the treatment and follow-up recommendations.